Strained DNA is kinked by low concentrations of Zn(2+) - Han, Wenhai (The National Academy of Sciences of the USA, 1997)
A novel atomic force microscope with a magnetically oscillated tip has provided unprecedented resolution of small DNA fragments spontaneously adsorbed to mica and imaged in situ in the presence of divalent ions. Kinks (localized bends of average angle 78°) were observed in axially strained minicircles consisting of tandemly repeated d(A)(5) and d(GGGCC[C]) sequences. The frequency of kinks in identical minicircles increased 4-fold in the presence of 1 mM Zn(2+) compared with 1 mM Mg(2+). Kinking persisted in mixed Mg(2+)/Zn(2+) electrolytes until the Zn(2+) concentration dropped below 100 μM, indicating that this type of kinking may occur under physiological conditions. Kinking appears to replace intrinsic bending, and statistical analysis shows that kinks are not localized within any single sequence element. A surprisingly small free energy is associated with kink formation.